The Air-Breathing Paradise Fish (Macropodus opercularis) Differs From Aquatic Breathers in Strategies to Maintain Energy Homeostasis Under Hypoxic and Thermal Stresses - Wang, Min-Chen; Lin, Hui-Chen (Frontiers in Physiology, 2018)
Two major strategies are used by most fish to maintain energy homeostasis under hypoxia. One is to utilize alternative metabolic pathways to increase energy production, and the other is to limit energy expenditure by suppressing energy-consuming processes, especially ionoregulation. Some anabantoid fishes live in tropical rivers, where hypoxic environments occur frequently. We previously found that under ambient hypoxia, anabantoid fishes do not downregulate Na+/K+-ATPase (NKA) activity to conserve energy in gills but instead increase the frequency of air-breathing respiration (ABR). In addition to the hypoxic condition, another factor that may cause cellular hypoxia in fish is abnormally high environmental temperatures. The frequency of such extreme thermal events has increased due to global climate change. In the present study, we examined whether the anabantoid fish, Macropodus opercularis employs the two strategies mentioned above to resist both ambient hypoxic and elevated thermal (cellular hypoxic) conditions. Results indicate that neither glucose metabolism nor gill NKA activity were altered by hypoxia, but glucose metabolism was increased by thermal stress. NH4+ excretion and ABR frequency were both increased under hypoxia, thermal or hypoxic-and-thermal treatments. In fish that were restricted from breathing air, increased mortality and glucose metabolism were observed under hypoxic or thermal treatments. These results suggest that for M. opercularis, increasing ABR is an important strategy for coping with unmet oxygen demand under hypoxic or thermal stress. This behavioral compensation allows anabanoid fish to physiologically withstand hypoxic and thermal stresses, and constitutes a mechanism of stress resistance that is unavailable to water-breathing fishes.